Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.energyfuels.2c01403
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Behavior of Single-Gas Hydrates in the Batch-type Stirred Reactor and Their Promotion Effect with Ultrafine Bubbles: A Mini Review and Perspectives

Abstract: Formation and dissociation processes of gas hydrates have been studied for managing the flow of natural gas and for developing new natural gas resources. Recently, such studies have also examined the unique properties of gas hydrates for use in industry, such as gas and energy storages. However, a large degree of supercooling (or supersaturation) and a long induction time are required to form gas hydrates even when their components (water and guest gas) are in hydrate-forming conditions. To overcome these obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Still, compared to that of pure water, the freezing curve for UFB-included water shifted to a higher temperature by approximately 0.6 °C, which is just slightly larger than the temperature uncertainty. Thus, just as UFBs appear to promote gas-hydrate nucleation [ 15 , 16 , 17 , 18 , 19 ], the UFBs here may also promote ice nucleation. A possible promoting effect of UFBs may be caused by them providing a large area of the gas–liquid interface in water as potential nucleation sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, compared to that of pure water, the freezing curve for UFB-included water shifted to a higher temperature by approximately 0.6 °C, which is just slightly larger than the temperature uncertainty. Thus, just as UFBs appear to promote gas-hydrate nucleation [ 15 , 16 , 17 , 18 , 19 ], the UFBs here may also promote ice nucleation. A possible promoting effect of UFBs may be caused by them providing a large area of the gas–liquid interface in water as potential nucleation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-micrometer bubbles, known as ultrafine bubbles (UFBs) [ 10 ], have come under recent interest for various types of water treatment [ 8 , 11 , 12 , 13 , 14 ], and have been found to also promote the nucleation of the ice-like gas hydrates [ 15 , 16 , 17 , 18 , 19 ]. In the latter application, Uchida et al [ 15 ] found that the dissociation of gas hydrates generates a large amount of UFBs that, upon later investigation, were found to promote the nucleation of gas hydrates [ 16 , 17 , 18 , 19 ]. Although UFBs were thought to rapidly collapse before they could affect crystal nucleation [ 20 , 21 ], Uchida and co-authors verified that they remain in the water long enough to promote nucleation [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan et al 29 analyzed natural gas hydrate samples spatially resolved using Raman spectroscopy to identify whether these natural samples only show heterogeneity with regard to their cage occupancy and composition or whether they already show coexistent phases. In a mini review, Uchida et al 30 summarized the technologies for promoting the nucleation process in gas hydrate formation in addition to an account of recent studies on ultrafine bubbles to reduce induction time. Kim et al 31 ■ ENERGY Methane gas exists in permafrost as crystalline clathrate compounds, and thus, they are a promising unconventional resource of natural gas.…”
Section: ■ Fundamentalsmentioning
confidence: 99%
“…Pan et al analyzed natural gas hydrate samples spatially resolved using Raman spectroscopy to identify whether these natural samples only show heterogeneity with regard to their cage occupancy and composition or whether they already show coexistent phases. In a mini review, Uchida et al summarized the technologies for promoting the nucleation process in gas hydrate formation in addition to an account of recent studies on ultrafine bubbles to reduce induction time. Kim et al examined tetrahydrofuran (THF) + methanol clathrate formed from 27 mol % NH 4 F aqueous solution with PXRD and molecular dynamics simulations to investigate the effect of methanol guest molecules on the thermal properties of ammonium-fluoride-doped THF clathrate hydrates.…”
Section: Fundamentalsmentioning
confidence: 99%